Offshore Wind Farms - Negro Valdecantos, Vicente; Esteban, María Dolores; López-Gutiérrez, José-Santos (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The coastal zone is the host to many human activities, which have significantly increased in the last decades. However, sea level rise and more frequent storm events severely affect beaches and coastal structures, with negative consequences and dramatic impacts on coastal communities. These aspects add to typical coastal problems, like flooding and beach erosion, which already leading to large economic losses and human fatalities. Modeling is thus fundamental for an exhaustive understanding of the nearshore region in the present and future environment. Innovative tools and technologies may help to better understand coastal processes in terms of hydrodynamics, sediment transport, bed morphology, and their interaction with coastal structures. This book collects several contributions focusing on nearshore dynamics, and span among several time and spatial scales using both physical and numerical approaches. The aim is to describe the most recent advances in coastal dynamics.